A Study on Impact of Earnings Announcements on Share Prices in Indian Stock Market - Sharanappa, Jalihal; Naik, Mallikarjun (International Journal of Membrane Science and Technology, 2023)
We made an attempt to examine the stock prices response to quarterly earnings announcements in Indian stock market. To test the market efficiency, the event study methodology is applied and the abnormal returns are measured using the market model method. We have included NSE nifty 500 companies as sample. We observed that the majority of days during the prior to and post-announcement periods, the Abnormal returns are positive and significant. That implies that investors may experience unusual gains as a result of earnings news. So, we came to the conclusion that the Indian stock market is inefficient at the semi-strong level.